Pengembangan Karier Guru Selama dalam Jabatan: Analisis Kompetensi Profesional - Nina Rahayu; Elvina Hawari; Aliyas Aliyas (Al-Musannif, 2022)
The work of the teaching profession cannot be done by people who do not have special skills or have not studied teacher education. This study aims to analyze teacher career development while in position and focuses on: (1) the educational profession; (2) teacher professional competence; and (3) teacher professional development. This literature study uses a pedagogic and juridical approach. Data collected through book and journal documentation was analyzed using content analysis techniques. The results of the study found that the development of teacher professionalism is an unavoidable condition, like the changing times. Improving teachers' professional abilities is accomplished with government assistance through programs and training activities (providing opportunities). Improving teachers’ professional abilities should not only focus on administrative aspects of staffing, but also on increasing their professional abilities and commitment as educators. Efforts to improve teacher professionalism certainly require support from all parties, including professional organizations, the government, and the community. This research has implications for teachers as a competitive profession that demands development according to the times; therefore, teachers must consciously and responsibly always want to improve their professionalism.